The province in Boyacá: territorial, historical and functional unit of planning in the management of endogenous regional development, 2004-2011 - Estupiñan Pedraza, Lorena Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article analyzes the province as a territorial dimension of development in Boyacá. First, the province is described as a territorial (specific site of action), historical (transcendent) and functional unit (with specific uses). Secondly, the concept of planning in the management of endogenous regional development is exposed, in order to analyze it from the province. Therefore, it is established that “to achieve a sustainable social change that will lead in the development of a region” is necessary to start from the activation of the internal capabilities including the organization of the territory, which in Boyacá is the province and that is from the province that the departmental development should be planned.